Including Occupational Risk Assessment in The Workstation Description Sheet as A Factor Contributing to Increasing the Risk Perception of Employees - Wiktoria CZERNECKA (Communications of International Proceedings, 2022)
The occupational risk assessment is a mandatory document that the employer should present to employees. It should contain the most important information on threats at workplaces and their assessment using the selected method. The occupational risk assessment should be available to all employees and periodically reviewed and updated, especially after changes occur at the workplace that may generate new risks. An important element in the development of the risk assessment should be its presentation in a way that is accessible and understandable for the employee, along with appropriate references facilitating the interpretation of the results obtained on the basis of the application of the assessment method selected by the enterprise. Often, however, problems are noticed in this area, resulting, among others, from inaccurate implementation of the risk assessment, presenting it in an incomprehensible manner or not updating it after significant changes in the workplace. This article presents the concept of including occupational risk assessment in a workstation description sheet in terms of occupational health and safety, together with the results of research conducted among employees of a large manufacturing company on how they assess the introduction of this change in the context of increasing their perception of risk at work.
Keywords: occupational health and safety; occupational risk assessment; workplace safety; safety culture; risk factors